Valuative scope of the test in the extraordinary appeal of cassation - Rodríguez Cedeño, María José (2025)
The cassation appeal aims to allow a new examination of evidence to achieve a better understanding of the facts and ensure more reliable justice. To this end, it considers the constitutive elements of violations of the system of sound criticism. The objective of this study is to determine the evaluative scope of evidence in the extraordinary cassation appeal. Methodologically, a descriptive and explanatory approach was adopted to characterize the issue under study. A documentary research design was employed, aimed at recovering and analyzing data previously obtained and recorded by other researchers to support the study’s foundations. Additionally, a dogmatic legal study was conducted, enabling a direct analysis of the cassation rule to examine its interpretation and application in the judicial field. Regarding the results, it was demonstrated how errors in the application of sound criticism justify a new review of evidence by the supreme judicial body, as they constitute material injustice. In conclusion, the cassation appeal contributes to the realization of justice by considering less abstract legal elements. Furthermore, jurisprudence and legal doctrine allow for the identification of evidentiary evaluation flaws that may hinder the proper application of the law.